Icariin Research Trends: Bibliometric Analysis - Septiana Indratmoko; Laela Hayu Nurani; Iis Wahyuningsih; Rochany Septiyaninsih (Postgraduate, University of Mataram, 2023)
Icariin is a compound with various pharmacological effects, such as anti-osteoporosis, cardiovascular protection, anti-inflammatory, antitumor, immunoprotection, and sexual dysfunction improver. Over the past decades, several publications and literatures have studied the compound and its potential effects. This is a bibliometric analysis of academic studies related to icariin compounds, and their productivity. Therefore, this research aims to comprehensively analyse the findings of several articles related to icariin globally. The articles used were obtained from the Scopus database using the keywords